Associations of dietary and sedentary behaviours of pregnant women with their children's birth weight: findings from the CHAT trial in Australia - Huilan Xu; Limin Buchanan; Yong Wang; Philayrath Phongsavan; Louise A Baur; Li Ming Wen (Cambridge University Press, 2023)
Abstract Objective: To examine the associations of pregnant women's dietary and sedentary behaviours with their children's birth weight. Design: Secondary data analysis was conducted using data from a randomised controlled trial, Communicating Healthy Beginnings Advice by Telephone, conducted in Australia. Information on mothers' socio-demographics, dietary and sedentary behaviours during pregnancy was collected by telephone survey at the third trimester. Birth weight data were extracted from the child's health record book. Multinomial logistic regression models were built to examine the associations of pregnant women's dietary and sedentary behaviours with children's birth weight. Setting: Participating families. Participants: Pregnant women and their children. Results: A total of 1132 mother-child dyads were included in the analysis. The majority of infants (87 %, n 989) were of normal birth weight (2500 g to <4000 g), 4 % (n 50) had low birth weight (<2500 g) and 8 % (n 93) had macrosomia (≥4000 g). Mothers who ate processed meat during pregnancy were more likely to have macrosomia (adjusted risk ratio (ARR) 1·80, 95 % CI (1·12, 2·89)). The risk of macrosomia decreased as the number of dietary recommendations met by mothers increased (ARR 0·84, 95 % CI (0·71, 0·99)). Children's birth weight was not associated with mothers' sedentary time. Children's low birth weight was not associated with mothers' dietary and sedentary behaviours during pregnancy. Conclusion: Maternal consumption of processed meat during pregnancy was associated with an increased risk of macrosomia. Increasing number of dietary recommendations met by mothers was associated with a lower risk of macrosomia. The findings suggested encouraging pregnancy women to meet dietary recommendation will benefit children's birth weight.